A Double-Blind Trial of Intramuscular Stanozolol in the Prevention of Postoperative Deep Vein Thrombosis Following Elective Abdominal Surgery - Blarney, S L; McArdle, B M; Burns, P; Carter, D C; Lowe, G D O; Forbes, C D (Thrombosis and Haemostasis, 1984)
Fibrinolytic shutdown may be important in the development of postoperative deep vein thrombosis (DVT). We have previously shown that stanozolol 50 mg, given intramuscularly 24 hr before surgery, prevents the decrease in plasminogen activator activity (PA) seen on the first postoperative day in patients at high risk of DVT. To investigate the role of fibrinolytic shutdown in causation of DVT, sixty patients were randomised in a double-blind controlled trial to receive stanozolol or placebo intramuscularly, and DVT was detected by leg scanning and confirmed by venography. Scan positive DVT occurred in IT of 31 placebo patients (35%) and 12 of 29 who received stanozolol (41%). A significant decrease in PA was confirmed in the placebo group, while stanozolol caused a significant increase in PA on the first postoperative day. Patients in either group who did not develop DVT showed minimal changes in PA. We conclude that prevention of fibrinolytic shutdown by this regimen of stanozolol does not prevent postoperative DVT, and that further studies are required to clarify the relationships of postoperative fibrinolysis and DVT.
Keywords: Fibrinolysis; Plasminogen activator; Deep vein thrombosis